Strengthening Nationalism and National Awareness of Students at State Senior High School 3, Medan City, Through the Implementation of the Pancasila Geopolitics Module Learning - Amin, Muryanto; Dahlan Ritonga, Alwi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The goal of this program is to assist Indonesian education, specifically SMAN 3 Medan, in overcoming the challenge posed by students' diminished sense of national awareness and dwindling sense of nationalism. Participatory learning and action (PLA) and socialization are the methods employed in this service. The Geopolitics of Pancasila module will be taught to students of SMAN 3 Medan. This school consistently receives nominations for Medan City's top 10. The target to be achieved through this service is to increase quality education that is in accordance with the standardization of the success of the world's SDGs. Additionally, it instills in the next generation a greater sense of nationalism and national awareness, making them more concerned with upholding Pancasila values in their daily lives.